2006
DOI: 10.1086/498579
|View full text |Cite
|
Sign up to set email alerts
|

Gene‐Expression Profiling Discriminates between Cerebral Malaria (CM)–Susceptible Mice and CM‐Resistant Mice

Abstract: The development of cerebral malaria (CM) in mice with Plasmodium berghei ANKA infection is under genetic control. Brain gene-expression patterns were investigated in well-defined genetically CM-resistant (CM-R; BALB/c and DBA/2) and CM-susceptible (CM-S; C57BL/6 and CBA/J) mice by use of cDNA microarrays. By combining transcriptional profiling with rigorous statistical methods and cluster analysis, we identified a set of 69 genes that perfectly discriminated between mouse strains and between CM-R and CM-S mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
55
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 61 publications
4
55
0
Order By: Relevance
“…The findings of Lovegrove and colleagues 4 thus confirm the findings in the two previous murine CM microarray studies that IFN and IFN-regulating processes play a major role in murine CM pathogenesis. Interestingly, although earlier murine studies have implicated TNF-␣ in CM pathogenesis, 10 and TNF-related or TNF-induced genes were among the genes up-regulated in CM-susceptible but not CM-resistant mice in the study by Delahaye and colleagues, 23 TNF-␣-related genes were not a major part of the interactome hubs in the study by Lovegrove and colleagues. 4 In contrast, neither any of the caspase genes nor Fas (Cd95) was noted to be up-regulated in the studies by Delahaye and colleagues 23 or Sexton and colleagues.…”
Section: Pitfalls Of Microarray Analysis: Comparing Murine CM Studiesmentioning
confidence: 79%
See 2 more Smart Citations
“…The findings of Lovegrove and colleagues 4 thus confirm the findings in the two previous murine CM microarray studies that IFN and IFN-regulating processes play a major role in murine CM pathogenesis. Interestingly, although earlier murine studies have implicated TNF-␣ in CM pathogenesis, 10 and TNF-related or TNF-induced genes were among the genes up-regulated in CM-susceptible but not CM-resistant mice in the study by Delahaye and colleagues, 23 TNF-␣-related genes were not a major part of the interactome hubs in the study by Lovegrove and colleagues. 4 In contrast, neither any of the caspase genes nor Fas (Cd95) was noted to be up-regulated in the studies by Delahaye and colleagues 23 or Sexton and colleagues.…”
Section: Pitfalls Of Microarray Analysis: Comparing Murine CM Studiesmentioning
confidence: 79%
“…Interestingly, although earlier murine studies have implicated TNF-␣ in CM pathogenesis, 10 and TNF-related or TNF-induced genes were among the genes up-regulated in CM-susceptible but not CM-resistant mice in the study by Delahaye and colleagues, 23 TNF-␣-related genes were not a major part of the interactome hubs in the study by Lovegrove and colleagues. 4 In contrast, neither any of the caspase genes nor Fas (Cd95) was noted to be up-regulated in the studies by Delahaye and colleagues 23 or Sexton and colleagues. 22 The brain tissue microarray studies performed thus far in murine CM show a number of similarities and most strikingly point to IFN-regulating and IFN-regulated processes as critical to CM, but they also differ in their findings.…”
Section: Pitfalls Of Microarray Analysis: Comparing Murine CM Studiesmentioning
confidence: 79%
See 1 more Smart Citation
“…cDNA microarray analysis from brain tissue performed in genetically resistant (CM-R) and susceptible (CM-S) mice identified 327 genes discriminated between infection stages, mouse strains and CM-R and CM-S phenotypes (Delahaye, Coltel et al 2006;Delahaye, Coltel et al 2007). Analysis of these 327 genes using expression analysis systematic explorer (EASE) software revealed that the clustered genes were biologically relevant to the defense response such as the response to malaria, inflammatory and immune response, and metabolism like oxidative phosphorylation, glycolysis/gluconeogenesis or tryptophan metabolism.…”
Section: Gene-expression Profiling and CMmentioning
confidence: 99%
“…2 Transcript profiling experiments have documented a substantial pro-inflammatory response that is more pronounced in susceptible mice. [7][8][9] In addition, loss-of-function mutations in genes coding for pro-inflammatory molecules such as interferon-g (Ifng), lymphotoxin (Lta), hemolytic complement (C5a) and interferon regulatory factor 1 (Irf1) have been shown to protect against CM. [10][11][12][13] These observations support the hypothesis of for a central function for immune-mediated pathology in CM, with T cells, platelets and resident macrophages implicated in inflammatory response and tissue injury.…”
mentioning
confidence: 99%